Pembuatan Aplikasi Reservasi Tempat Berbasis Web Di Lemme Get Space Café - Rifati Rahma (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Now, the development of technology is very high. The impact of these developments affects to various fields including business. Now, humans are trying to increase their creativity and activities by using more efficient tools, i.e computers and networks. The use of computers as a data processing tool is much recommended, because it can facilitate work that make efficiency of energy and time is achieved in data processing. No exception for fields include F&B such as cafes and restaurants. This study aims to take advantage of technology developments to process data and information using computers and networks so it can be used for cafe and restaurant businesses by creating a web-based information system application that will be used to make booking. Scope of design and implementation for this web-based reservation application is limited to incomplete functions.